A comprehensive assessment of source material for apple breeding for immunity and fruit quality - E. V. Ulyanovskaya; T. G. Prichko; L. D. Chalaya (Вавиловский журнал генетики и селекции)
The results of years of studying new and promising varieties of Apple trees (Malus domestica Borkh) grown in Southern Russia. Evaluation of Apple cultivars was carried out for resistance to the major fungal pathogens scab (Venturia inaequalis (Cooke) G. Winter) and powdery mildew (Podosphaera leucotricha Salm.), the quality and marketability of fruits, the content of biologically active substances underlying the antioxidant  properties of fruits. An advanced method of polyploidy based on inclusion of parental forms with immunity to scab was applied in Apple selection. Integrated assessment of key biological traits of varieties and forms of Apple with diverse ploidy in unstable environments resulted in a selection of donors and sources of significant characteristics for Apple breeding such as resistance and immunity to major fungal pathogens, large fruit, bright red color of the fruit, improved chemical composition. High-quality varieties of Apple breeding in SKZNIISiV together with VNIISPK combining immunity to scab (the Vf gene) with high resistance to powdery mildew were selected: Fortune, Amulet, Carmen, Nika, Margo, Orfei, Souyz and others. Apple-tree grades, immune to scab, with a high viability of pollen (83–98%) were revealed: Azimuth, Vasilisa, Carmen, Lubava, Margo, Fortune, Liberty, Prima, Florina, Freedom. The promising parental forms passing to most of their hybrid progeny good tastes of fruits are Golden Delicious tetraploid, Wealthy tetraploid, Belle de Boskoop, Balsgard 0247 E, Papirovka tetraploid, and diploidy grades to Alkmene, Prima, Redfree and Kuban. Apple cultivars were revealed with high chemical indicators including the content of sugars: Orfei (10.8 %), Champion (10.5 %); vitamin C: Vasilisa and Souyz (more than 9.0 mg/100 g), hybrid form 44-24-49-uy (more than 11.4 mg/100 g); and P-active substances – Vasilisa, Lubava, Margo (more than 110.0 mg/100 g), whose use in breeding programs encourages the rapid creation of new genotypes with improved biochemical composition of fruits.